2020
DOI: 10.6007/ijarbss/v10-i10/8022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Awareness on Green Practices: A Study Among Homestay Operators in Selangor

Abstract: Homestay is a human-oriented service industry. This industry partially contributes to environmental issues, especially through its day-to-day operations which involve the consumption of resources such as water and energy. Increasing tourist arrivals will also add on to the impact on the environment. In recent times, demand from consumers for eco-friendly accommodation has increased. However, some accommodation managers still operate in an outdated manner and do not fully recognise or fully appreciate the deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This is in agreement with the findings of Foris et al (2020) who stated that implementing environmentally sustainable practices brings new challenges like associated costs, although some new opportunities emerge. Dwivedi et al (2022) and Yusuf et al (2020) reported that one of the bottlenecks for effective implementation of green practices is high costs involved. High maintenance costs were followed by inadequate presence of trainers (CV = 25.4) which affected smooth implementation of green practices (Aripin et al, 2018).…”
Section: Benefits Obtained By the Five-star Hoteliers As A Results Im...mentioning
confidence: 99%
“…This is in agreement with the findings of Foris et al (2020) who stated that implementing environmentally sustainable practices brings new challenges like associated costs, although some new opportunities emerge. Dwivedi et al (2022) and Yusuf et al (2020) reported that one of the bottlenecks for effective implementation of green practices is high costs involved. High maintenance costs were followed by inadequate presence of trainers (CV = 25.4) which affected smooth implementation of green practices (Aripin et al, 2018).…”
Section: Benefits Obtained By the Five-star Hoteliers As A Results Im...mentioning
confidence: 99%